2022
DOI: 10.7554/elife.74951
|View full text |Cite
|
Sign up to set email alerts
|

Response to comment on ‘SARS-CoV-2 suppresses anticoagulant and fibrinolytic gene expression in the lung’

Abstract: Early in the SARS-CoV-2 pandemic, we compared transcriptome data from hospitalized COVID-19 patients and control patients without COVID-19. We found changes in procoagulant and fibrinolytic gene expression in the lungs of COVID-19 patients (Mast et al., 2021). These findings have been challenged based on issues with the samples (Fitzgerald and Jamieson, 2022). We have revisited our previous analyses in the light of this challenge and find that these new analyses support our original conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As SERPING1 is one of the proteins with the highest connectivity in the SARS-CoV-1 and SARS-CoV-2 interactomes, it was proposed that SARS-CoV-2 infection directly causes deficiency in C1 esterase inhibitor ( Thomson et al, 2020 ). Recently, clinical samples of COVID-19 patients revealed C1-Inhibitor as one of the most prominently downregulated genes with 80-fold decreased expression ( Mast et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As SERPING1 is one of the proteins with the highest connectivity in the SARS-CoV-1 and SARS-CoV-2 interactomes, it was proposed that SARS-CoV-2 infection directly causes deficiency in C1 esterase inhibitor ( Thomson et al, 2020 ). Recently, clinical samples of COVID-19 patients revealed C1-Inhibitor as one of the most prominently downregulated genes with 80-fold decreased expression ( Mast et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, induction of CAS along with downregulation of KKS inhibitor SERPING1 and des-Arg-Kinin inactivator ACE2 may lead to local excess of DAK, resulting in constitutive activation and induction of its receptor B1R ( Figure 1B ). Indeed, clinical samples from COVID-19 patients revealed that B1R was one of the most prominently upregulated genes with a 260-fold expression increase ( Mast et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%